Comparative transcriptome analysis of rubber tree (Hevea brasiliensis) between high and low yield rubber clones related to natural rubber biosynthesis - Mohd Fahmi Abu Bakar
Hevea brasiliensis or rubber tree is a well-known species belonging to the Euphorbiaceae family are native to Amazon rainforest. The species which has contributed a major share to the agricultural economy of Malaysia since 1950s because of the ability to produce natural rubber with high economic value. Natural rubber has special pr pertie such as flexible, high elasticity and efficient heat dispersion due to presence of cis-l,4-polyisoprene. Cis-1,4-polyisoprene is synthesized via two biosynthesis pathways; isoprenoid and rubber biosynthesis pathways. The high produetsea f cis-1 ,4-polyisoprene within rubber tree are found to be related to high latex production. In addition, several other factors including transcription factors involvement and sucrose transport to the laticifer cell may played some role in the high latex production. Since the high latex production is related to the rubber biosynthesis at genetic level, the main limiting factors in the natural rubber production are still discussed. However, there are still lack of infon.iation about expression of genes related to rubber biosynthesis which can help to understand how high latex production can be achieved at genetic level. Therefore, this study is focussing on gaining some knowledge and important information related to genes that control natural rubber production. The knowledges are related to biosynthesis pathways involved, relationships of the tissues and expression of genes related to natural rubber production which is very important for development of high yield rubber clone through rubber breeding program. A total of twelve specimensfrom bark, leaf and latex tissues ofRRIM 3001 and RRIM 712 were isolated for total RNA. Each specimen was then sent for RNA sequencing through paired-end sequencing on the Illumina NextSeq 500 and generated a mean of 75,742.501 raw reads. The quality assessment of raw reads was performed and a mean of 73 ,816,244 of clean reads used for further analysis. The clean reads were then assembled using Cufflink program to generate 101,269 transcripts. The 101,269 transcripts were annotated using several databases including NCB I (National Center of Biotechnology .Jnfonnation), UniProt-SwissProt (Universal Protein Resources), GO (Gene Ontology), KEGG (Kyoto Encyclopedia of Genes and Genomes) and Pfam (Protein Domain) using Blast2GO program to find genes name and other information. The differential expression analysis between tissues of RRIM 3001 and RRIM 712 was then performed to find expression of genes involved in isoprenoid biosynthesis through Mevalonate (MVA) and 2-C-methyl-D-erythritol 4-phosphate (MEP) pathways as well as rubber biosynthesis 'pathways. The analysis showed that Acetyl-CoA-Acetyltransferase (AAC ) and Diphosphomevalonate Decarboxylase (MVD) genes via MV A pathway while Small Rubber Particle Protein (SRPP) and Rubber Elongation' Factor (REF) genes through rubber biosynthesis pathway have the highly expressed within bark, leaf and latex tissues of RRIM 3001 compared to RRIM 712. Ethylene Response Factor (ERF), a transcription factor was also found expressed highly within high yield clone (RRIM 3001) than low yield clone (RRIM 712). The quantitative amplification analysis was done to validate the five selected genes using rubber clones with high, moderate and low yield characteristics. The expression of five genes were directly proportional to the yield characteristics. Therefore, the five selected genes could be used for determination of new rubber clone with high latex yield characteristics.